2022
DOI: 10.3390/buildings12060704
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Performance of Rib Beam Bridge Slabs Reinforced with Polyurethane Concrete Based on the Damage Theory

Abstract: In this paper, the rib beam bridge slabs were taken as the research object. Static load and fatigue tests were carried out on the benchmark bridge slabs to determine the ultimate load capacity and fatigue life of the bridge slabs. Then, the bridge slab was pre-damaged and reinforced with polyurethane concrete. A fatigue test was carried out on the reinforced bridge slab to study the fatigue performance. Based on the damage theory, the fatigue damage reinforcement finite element models of the bridge slabs under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Therefore, polyurethanes are polymers available for many technical applications requiring flexibility, durability, and impact resistance [ 3 , 4 , 5 ]. Studies showed that polyurethane elastomers synthesized by macromolecular MDI and polyether have good hydrolysis resistance and low temperature flexibility, and are widely used in the construction field [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, polyurethanes are polymers available for many technical applications requiring flexibility, durability, and impact resistance [ 3 , 4 , 5 ]. Studies showed that polyurethane elastomers synthesized by macromolecular MDI and polyether have good hydrolysis resistance and low temperature flexibility, and are widely used in the construction field [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%